Aldehyde/ketone-catalyzed highly selective synthesis of 9-monoalkylated fluorenes by dehydrative C-alkylation with primary and secondary alcohols. Issue 3 (28th November 2016) - Chen, Jianhui; Li, Yang; Li, Shuangyan; Liu, Jianping; Zheng, Fei; Zhang, Zhengping; Xu, Qing
Abstract : Carbonyl compounds efficiently catalyze the dehydrative 9- C -alkylation of fluorenes with various primary and secondary alcohols to provide the useful 9-monoalkylated fluorenes in high selectivities. Abstract : By using aldehydes or ketones as the catalyst and screening CsOH out as the more effective base than KOH in many instances, an efficient 9- C -alkylation of fluorenes with alcohols was achieved to provide a green and practical method for general synthesis of the useful 9-monoalkylated fluorenes in high selectivities. This new method tolerates a wide range of substrates including activated and unactivated primary and secondary alcohols, thus solving the issues remaining in the field and largely broadening the diversity of the 9-monoalkylated fluorenes. Consequently, fine-tuning of the alkylated fluorenes was made possible to provide specific fluorene monomers for function-oriented polyfluorenes. Preliminary mechanistic studies revealed that the external carbonyl compounds can be quantitatively regenerated and recovered in the reaction cycle.